The value of the Ramsey number R5(C6) - Sun, Yongqi; Yang, Yuansheng; Wang, Zhihai (Utilitas Mathematica, 2008)
The multicolor Ramsey number Rr(H) is defined to be the smallest integer n = n(r) with the property that any r-coloring of the edges of the complete graph Kn must result in a monochromatic subgraph of K n isomorphic to H. It is well known that R2(C6) = 8, R3(C6) = 12 and R4C6) ≤ 21. In this paper, we prove that R5(C6) = 26.